1968
DOI: 10.1677/joe.0.0400505
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Concentrations in the Arterial Plasma of Guinea-Pigs During the Oestrous Cycle

Abstract: The quantities of circulating progesterone and its 20-dihydro metabolites in cyclic female guinea-pigs were estimated by gas chromatography with electron capture detection. Forty-four animals were divided into 13 groups of approximately equal size according to stage of the oestrous cycle. The day on which a lordosis response could be elicited was designated Day 0 of the cycle. In the first few hours of sexual receptivity on Day 0 progesterone levels were 0\m=.\36\ m=+-\ 0\m=.\07 \g=m\g./100 ml. arterial plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
32
1

Year Published

1969
1969
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 22 publications
8
32
1
Order By: Relevance
“…565-567). Progesterone concentration in plasma and ovarian tissue in the guinea-pig has been reported by Rowlands & Short (1959), Heap & Deanesly (1966), Heap, Perry & Rowlands (1967) and Feder, Resko & Goy (1968). The present study examines the progesterone levels in arterial plasma and in the CL of a few cyclic cuis and a small series of pregnant cuis.…”
Section: Introductionmentioning
confidence: 56%
“…565-567). Progesterone concentration in plasma and ovarian tissue in the guinea-pig has been reported by Rowlands & Short (1959), Heap & Deanesly (1966), Heap, Perry & Rowlands (1967) and Feder, Resko & Goy (1968). The present study examines the progesterone levels in arterial plasma and in the CL of a few cyclic cuis and a small series of pregnant cuis.…”
Section: Introductionmentioning
confidence: 56%
“…Vaginal epithelial cycles and the hormone changes associated with these cycles have been character¬ ized for many spontaneously ovulating rodents (Feder, Goy & Resko, 1967;Feder, Resko & Goy, 1968; Leavitt & Blaha, 1970;Lukaszewska & Greenwald, 1970;Challis, Heap & Illingworth, 1971; Baranczuk & Greenwald, 1973;Butcher, Collins & Fugo, 1974;Campbell, Ryan & Schwartz, 1976). In these rodents, the regular follicular cycles associated with spontaneous ovulation are reflected in predictable changes in plasma oestrogen and progesterone and, consequently, in changes in vaginal epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that there is a significant elevation of plasma progesterone (P 4 ) coincident with the luteal phase (dioestrus) in guinea pigs (Feder et al 1968;Challis et al 1971;Blatchley et al 1976;Garis and Foreman 1984), whereas fluctuations of plasma oestradiol (E 2 ) levels occur throughout the oestrous cycle (Chalis et al 1971;Croix and Franchimont 1975;Garris and Foreman 1984;Westfahl and Vekasy 1988;Hutz et al 1990).…”
mentioning
confidence: 99%